2006
DOI: 10.1039/b514190g
|View full text |Cite
|
Sign up to set email alerts
|

Structural, spectroscopic, and electrochemical behavior of trans-phenolato cobalt(iii) complexes of asymmetric NN′O ligands as archetypes for metallomesogens

Abstract: In order to understand and predict structural, redox, magnetic, and optical properties of more complex and potentially mesogenic electroactive compounds such as [Co(III)(L(t-BuLC))2]ClO4 (1), five archetypical complexes of general formula [Co(III)(L(RA))2]ClO4, where R = H (2), tert-butyl (3), methoxy (4), nitro (5), and chloro (6), were obtained and studied by means of several spectrometric, spectroscopic, and electrochemical methods. The complexes 2, 4, and 6 were characterized by single-crystal X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 48 publications
9
45
1
Order By: Relevance
“…The average area per molecule at collapse (A c ) was obtained by extrapolating the steepest part of the curve down to zero pressure. [3,14] The pyridine head-group of the ligand seems to have interfered little with the packing of the monolayer, and the observed area of [23][24][25] 2 molecule À1 is comparable to the packing reported for a carboxylic acid with an equivalent number of carbon atoms. [40] The formal film collapse happened at 45-50 mN m…”
Section: Q3dmentioning
confidence: 85%
See 1 more Smart Citation
“…The average area per molecule at collapse (A c ) was obtained by extrapolating the steepest part of the curve down to zero pressure. [3,14] The pyridine head-group of the ligand seems to have interfered little with the packing of the monolayer, and the observed area of [23][24][25] 2 molecule À1 is comparable to the packing reported for a carboxylic acid with an equivalent number of carbon atoms. [40] The formal film collapse happened at 45-50 mN m…”
Section: Q3dmentioning
confidence: 85%
“…In recent years, our groups have spearheaded systematic research in this area by focusing on a comprehensive approach that encompasses synthesis, [25] modeling, [26] and surface behavior. We have demonstrated the feasibility of Langmuir-Blodgett (LB) films with magnetic copper(II) clusters, [27] the redox-state control and dependence of a collapse mechanism on cobalt(II) films, [28] and the factor that determines the delicate equilibrium between redox activity and amphiphilicity in copper/phenoxyl species.…”
Section: CL 2 a C H T U N G T R E N N U N G (L Pyc 14 )] (3) [Cu mentioning
confidence: 99%
“…Similarly, the archetypical ligands were synthesized with 80-85 % yields following literature procedures [17,20,21] and characterized by means of ESI mass spectrometry, 1 H NMR, and infrared spectroscopy. ticularly visible at low cone voltages.…”
Section: The Ligandsmentioning
confidence: 99%
“…[13,14] At the forefront of this area, our group has focused on synthetic, modeling, and surface protocols involving the incorporation of magnetic µ-oxo-Cu 4 clusters in LangmuirBlodgett films, [15,16] the observation of distinctive collapse mechanisms on cobalt(II) films, [17] and the design of redoxactive copper-containing amphiphiles. [18,19] In a series of studies with iron(III), [20] cobalt(II/III), [21] and gallium-(III) [22] we have demonstrated that structural and electronic effects can determine the preferential geometry of redoxactive asymmetric NNЈO ligands in [ML 2 ] metallosurfactants. Structural rigidity of the ligand takes precedence to the electronic configuration of the metal ion and favors meridional coordination when asymmetric amines and imines are compared.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic spectra of the Co (III) C1 and C2 give bands around 650 nm. This band is assigned to the transition 1 A 1g → 1 T 2 g, suggesting that there is an octahedral geometry around Co (III) ion 20 . Another band at around 396-438 nm refers to the charge transfer band in all the complexes 21 .…”
Section: Resultsmentioning
confidence: 94%